Representation, Figure of Speech and Similes In Literature: a Case Study of Animal Farm: Exploring the Use of Figures of Speech in George Orwell's Animal Farm (Journal of Advances and Scholarly Researches in Allied Education, 2011)
One of the aims of literary text is to say as much as possible as briefly as possible,means to say more in few words to achieve a maximumeffectiveness. In this case, figuresof speech, specifically symbol, metaphor and simile have an important role, as theyinclude  figurative  meaning  of words besides their  literary meaning.  In  this  article, representation, metaphors and similes in George Orwell's „Animal Farm‟ were studied to find out the effect of using figures of speech on the writer's style and the addressee'sunderstanding. For this aim, these three figures of speech were founded in the novel andtheir types were determined according to New mark’s (1988b), Fromilhague`s (1995) andRokni `s (2009)classifications, respectively.